Immunogenicity of the pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) administered concomitantly with the meningococcal serogroup B (4CMenB) vaccine in infants: A post-hoc analysis in a phase 3b, randomised, controlled trial. Issue 35 (14th August 2019) - Safadi, Marco Aurelio P.; Martinon-Torres, Federico; Weckx, Lily Yin; Moreira, Edson Duarte; da Fonseca Lima, Eduardo Jorge; Willemsen, Arnold; Toneatto, Daniela; Habib, Md Ahsan; Borys, Dorota
Highlights: PHiD-CV was co-administered with 4CMenB and/or MenC-CRM. PHiD-CV immunogenicity was assessed in a post-hoc analysis. Anti-pneumococcal antibody responses did not seem to be impacted by 4CMenB co-administration. Abstract: Background: No data are currently available on immunogenicity of higher-valent pneumococcal conjugate vaccines when co-administered with a 4-component meningococcal serogroup B vaccine (4CMenB). Methods: Post-hoc analysis of pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) immunogenicity when co-administered with 4CMenB (2 + 1 schedule) and/or a CRM-conjugated meningococcal serogroup C vaccine (MenC-CRM) in a trial assessing 4CMenB reduced schedules and co-administration with MenC-CRM (NCT01339923). Infants were randomized to receive 4CMenB and MenC-CRM (Group 1) or MenC-CRM (Group 2) at 3, 5, and 12 months (M) of age. Both groups received PHiD-CV (3 + 1 schedule) as part of the Brazilian national immunisation programme at 3 M, 5 M, 7 M, and 12 M of age. Antibody responses were assessed pre-vaccination, 1 M post-dose 2, pre-booster, and 1 M post-booster. Results: Anti-pneumococcal antibody responses were in similar ranges in the two study groups. Conclusions: 4CMenB co-administration did not seem to impact antibody responses to PHiD-CV in infants.